2020
DOI: 10.1021/acsaelm.0c00680
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Content on the Structure and Reliability of Ferroelectric HfxZr1–xO2 Layers

Abstract: Although some years have passed since the discovery of the ferroelectric phase in HfO 2 and ZrO 2 and their solid solution system Hf x Zr 1−x O 2 , the details of the emergence of this phase are still under investigation. Surface energy contribution, dopant inclusion, residual stress, electric field, and oxygen vacancies have been proposed and studied as potential factors that can influence the phase stabilization. In this work, Hf x Zr 1−x O 2 layers with different Hf/Zr ratios are deposited via atomic layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 41 publications
10
98
0
Order By: Relevance
“…This minimizes the amount of oxygen vacancies in the film and stabilizes nonferroelectric monoclinic phase portions as observed by GIXRD. [ 21,23 ] These monoclinic phase portions reduce the remanent ferroelectric polarization, which is in good correlation with the wake‐up model published by Pesic et al [ 12 ] The reason for the high depolarization field in films annealed in nitrogen atmosphere is predicted to be a tetragonal interfacial region formed by a high vacancy concentration at the interface. As there is only a slight reduction of the IrO 2 top electrode but no significant change in the oxygen vacancy level as observed in HAXPES, there seems to be limited oxygen out‐diffusion close to the electrode interface with annealing in nitrogen gas.…”
Section: Figuresupporting
confidence: 81%
See 2 more Smart Citations
“…This minimizes the amount of oxygen vacancies in the film and stabilizes nonferroelectric monoclinic phase portions as observed by GIXRD. [ 21,23 ] These monoclinic phase portions reduce the remanent ferroelectric polarization, which is in good correlation with the wake‐up model published by Pesic et al [ 12 ] The reason for the high depolarization field in films annealed in nitrogen atmosphere is predicted to be a tetragonal interfacial region formed by a high vacancy concentration at the interface. As there is only a slight reduction of the IrO 2 top electrode but no significant change in the oxygen vacancy level as observed in HAXPES, there seems to be limited oxygen out‐diffusion close to the electrode interface with annealing in nitrogen gas.…”
Section: Figuresupporting
confidence: 81%
“…[ 11,19–22 ] For pure HfO 2 , the amount of oxygen and oxygen vacancies within the film can significantly influence the stabilization of the crystalline phases. [ 21,23 ] It has been shown that oxygen‐rich films crystallize in the nonferroelectric monoclinic phase (m‐phase), whereas oxygen‐deficient films predominantly form in the tetragonal phase (t‐phase). The stabilization of the ferroelectric orthorhombic phase (o‐phase), however, seems to need a certain amount of oxygen vacancies in between these two extremes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Materano et al also found that increasing oxygen content in the growth atmosphere promoted the transition to monoclinic phase, whereas the tetragonal and orthorhombic phase were favored under oxygen‐deficient conditions. [ 98 ] Therefore, a lower incubation time reduces the crystallization temperature and larger nuclei are present in the as‐deposited hafnia thin films at room temperature. [ 41 ] Density functional theory (DFT) calculations also verified this correlation that tetragonal and orthorhombic phase formation is suppressed for higher oxygen concentrations in HfO 2 , and monoclinic phase nuclei are formed.…”
Section: Epitaxial Hafnia Thin Filmmentioning
confidence: 99%
“…Despite oxygen being heavily discussed as a key parameter for phase stabilization and reliability control both in traditional perovskite ferroelectrics and in newer HfO 2 -based materials, only lately the effect of the oxygen supply during film deposition has started to be studied systematically by tuning film growth processing parameters. [16][17][18] Within this review, first a general overview of oxygen related defects in oxides is presented. The next section presents the impact of the amount of these defects in terms of oxygen supply during deposition as shown through existing literature reports for undoped HfO 2 and differently doped HfO 2 layers.…”
Section: Introductionmentioning
confidence: 99%